2D‐on‐2D Al‐Doped NiCo LDH Nanosheet Arrays for Fabricating High‐Energy‐Density, Wide Voltage Window, and Ultralong‐Lifespan Supercapacitors - Huang, Xuejing; Chu, Bingxian; Han, Boming; Wu, Qingqing; Yang, Tianyi; Xu, Xuetang; Wang, Fan; Li, Bin (Small (Weinheim an der Bergstrasse, Germany), 2024)
Battery‐type electrode materials with high capacity, wide potential windows, and good cyclic stability are crucial to breaking through energy storage limitations and achieving high energy density. Herein, a novel 2D‐on‐2D Al‐doped NiCo layered double hydroxide (NiCoAlx LDH) nanosheet arrays with high‐mass‐loading are grown on a carbon cloth (CC) substrate via a two‐step hydro/solvothermal deposition strategy, and the effect of Al doping is employed to modify the deposition behavior, hierarchical morphology, phase stability, and multi‐metallic synergistic effect. The optimized NiCoAl0.1 LDH electrode exhibits capacities of 5.43, 6.52, and 7.25 C cm−2 (9.87, 10.88, and 11.15 F cm−2) under 0–0.55, 0–0.60, and 0–0.65 V potential windows, respectively, illustrating clearly the importance of the wide potential window. The differentiated deposition strategy reduces the leaching level of Al3+ cations in alkaline solutions, ensuring excellent cyclic performance (108% capacity retention after 40 000 cycles). The as‐assembled NiCoAl0.1 LDH//activated carbon cloth (ACC) hybrid supercapacitor delivers 3.11 C cm−2 at 0–2.0 V, a large energy density of 0.84 mWh cm−2 at a power density of 10.00 mW cm−2, and excellent cyclic stability with ≈135% capacity retention after 150 000 cycles. 2D‐on‐2D Al‐doped NiCo LDH nanosheet arrays with high‐mass‐loading delivers the high capacity of 7.25 C cm−2 under 0–0.65 V potential window. The as‐assembled hybrid supercapacitor delivers 3.11 C cm−2 at 0–2.0 V, a large energy density of 0.84 mWh cm−2 at 10.00 mW cm−2, and excellent cyclic stability with ≈135% capacity retention after 150 000 cycles.